IMMUNOGENICITY ANALYSIS OF TRITERPENE GLYCOSIDE FROM HOLOTHURIA ATRA TO DETECTING FAS AND BCL-2 PROTEIN ON THE SP-C1 CELL OF TONGUE CARCINOMA - Arma, Utmi; Satari, Mieke Hemiawati; Ilyas, Syafruddin; Handayani, Dian; Primasari, Ameta; Kasuma, Nila; Supriatno; A Gani, Basri (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this study is to assess the role of triterpene glycoside of Holothuria atra to induce the Fas and Bcl-2-regulated apoptosis in Supri's Clone 1 (Sp-C1) cell of tongue carcinoma. Methods: The triterpene glycoside of H. atra was isolated by high-performance liquid chromatography. The Sp-C1 cell of tongue carcinoma was cloned by Dulbecco's Modified Eagle Medium and cytotoxicity assay by 3-4-5-dimethylthiazol-2yl 2,5-diphenyltetrazolium bromide assay. Expression Fas and Bcl-2 protein were analysed by immunocytochemistry also apoptosis detected by double staining ethidium bromide acridine. The datum of studied was analyzed by one-way analysis of variance (ANOVA), significance (p<0.05), and strength correlation (p<0.001) with R=1. Results: The H. atra has triterpene glycoside, and in the dose of 4 mg/ml, it has been cytotoxic activities on the Sp-C1 (p<0.05), mortality 80%; inhibitory concentration 50 (IC50)=0.6 and anti-logarithm = 4. In general, the concentration of 2.5 mg/ml of triterpene glycoside has triggered the expression of Fas protein (active, 71%; moderate, 10%; and no-active, 27%), whereas the Bcl-2 protein (active, 59%; moderate, 14%; and no-active 27%). Statistically, both expressions of protein were significant (p<0.05). Triterpene glycoside caused the apoptosis of Sp-C1 cell (strong, 87%, and moderate, 13%). Conclusion: The triterpene glycoside has the properties of cytotoxicity, and apoptosis in the SP-C1 cell also could be triggering the expression of Fas and Bcl-2 proteins.